2011
DOI: 10.1002/mc.20812
|View full text |Cite
|
Sign up to set email alerts
|

Nimbolide retards tumor cell migration, invasion, and angiogenesis by downregulating MMP‐2/9 expression via inhibiting ERK1/2 and reducing DNA‐binding activity of NF‐κB in colon cancer cells

Abstract: Nimbolide, a plant-derived limonoid has been shown to exert its antiproliferative effects in various cell lines. We demonstrate that nimbolide effectively inhibited proliferation of WiDr colon cancer cells through inhibition of cyclin A leading to S phase arrest. It also caused activation of caspase-mediated apoptosis through the inhibition of ERK1/2 and activation of p38 and JNK1/2. Further nimbolide effectively retarded tumor cell migration and invasion through inhibition of metalloproteinase-2/9 (MMP-2/9) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 46 publications
5
90
1
Order By: Relevance
“…5C) [15]. Many studies had indicated that ERK1/2 and AKT were involved in activities of MMP2 and MMP9 [16,17,18]. To assess whether the suppressed expression of MMP2 and MMP9 was mediated by the inhibition of AKT and ERK1/2 pathways, we investigated the effect of AXIIR siRNA on phosphorylation of AKT and ERK1/2.…”
Section: Resultsmentioning
confidence: 99%
“…5C) [15]. Many studies had indicated that ERK1/2 and AKT were involved in activities of MMP2 and MMP9 [16,17,18]. To assess whether the suppressed expression of MMP2 and MMP9 was mediated by the inhibition of AKT and ERK1/2 pathways, we investigated the effect of AXIIR siRNA on phosphorylation of AKT and ERK1/2.…”
Section: Resultsmentioning
confidence: 99%
“…In our studies, we find that aspirin-mediated cell invasion inhibition is reversed by IKK-β overexpression, while the IKK inhibitor sensitizes the anti-invasive effect of aspirin in prostate cancer cells. In addition to NF-κB, there is abundant evidence that the invasive capacity of cancer cells is related to the activation of mitogen-activated protein kinases such as ERK1/2 [43]. Recent studies have demonstrated that the phosphorylation of ERK1/2 promotes MMP secretion and increases prostate cancer cell metastasis [44].…”
Section: Discussionmentioning
confidence: 99%
“…Nimbolide, a tetranortriterpenoid limonoid, is one of the important contributors to the cytotoxicity of neem extracts (20). This limonoid has been shown to possess numerous biological activities such as antifeedant (21), antimalarial (22), antimicrobial (23), and anticancer (19, 20, 2430) activities. The limonoid exhibits antiproliferative activity in a wide variety of tumor cells, including neuroblastoma, osteosarcoma, choriocarcinoma (31), cervical cancer (32), leukemia, and melanoma (29) cells.…”
Section: Introductionmentioning
confidence: 99%